PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA MELALUI SEMANGAT KERJA PEGAWAI PADA KANTOR PEMERINTAH KABUPATEN BOJONEGORO - Tony Ade Irawan; Hidayat Hidayat; Muninghar Muninghar (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to directly or indirectly transformational leadership, motivation and partial employee work towards employee performance. Furthermore, to examine the effect of transformational leadership style, work motivation and partial work spirit on employee performance. The population in this study were all employees of the Bojonegoro Regency Government. The sampling technique uses purposive sampling, which is the technique of sampling data with certain data. The sample in this study is because echelon II is 30 people. The results showed that transformational leadership style and work motivation were not significant to employee performance, while work motivation significantly affected the performance of Bojonegoro District Government employees. Transformationality leadership style cannot provide significant results on the performance of employees in the Bojonegoro District Government community. Motivation cannot provide significant results on the performance of employees in the Bojonegoro District Government. Transformational leadership style and work motivation are not significant to performance through spirit of work. Work motivation has a greater impasse on performance through a spirit of transformational work. Keywords: transformational leadership style, work motivation, spirit of work, performance